2015
DOI: 10.15517/rbt.v63i2.14160
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success of Cabralea canjerana (Meliaceae) in Atlantic forest fragments, Brazil

Abstract: Abstract:In Brazil, the Atlantic forest remnants have high biological diversity and a high level of endemism, but very little is known about the reproductive success of native species. Cabralea canjerana is a common tree in the Montane Atlantic forest, and its reproduction is highly dependent on pollinators. In order to contribute with the particular knowledge on this species, we collected data in three fragmented and three continuous forest sites, where the effects of fragmentation on both mutualistic (pollin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…Decreases in successful reproduction in fragmented forest environments have been associated with decreases in the qualities and quantities of pollinators found there (Aguillar & Galleto 2004). Similar results were observed with Cabralea canjerana (Meliaceae), which was visited by fewer pollinators, and demonstrated limited reproductive success in forest fragments when compared to continuous areas of Atlantic Forest (Franceschinelli et al 2015).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Decreases in successful reproduction in fragmented forest environments have been associated with decreases in the qualities and quantities of pollinators found there (Aguillar & Galleto 2004). Similar results were observed with Cabralea canjerana (Meliaceae), which was visited by fewer pollinators, and demonstrated limited reproductive success in forest fragments when compared to continuous areas of Atlantic Forest (Franceschinelli et al 2015).…”
Section: Discussionsupporting
confidence: 76%
“…Numerous studies have demonstrated that edge effects reduce the availability of abiotic resources such as water and soil nutrients (Dunley et al 2009;Athayde & Morellato 2014;Aizen & Feinsinger 1994;Franceschinelli et al 2015), and diminish fruit set as compared to that seen in the forest interior (Dunley et al 2009;Athayde & Morellato 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the effective of population sizes of the mountain white-eye (Zosterops poliogaster) in East Africa were higher in larger and interconnected forest patches (Husemann et al, 2015). Habitat fragmentation can also decrease fecundity in plants (Somanathan and Borges, 2000;Franceschinelli et al, 2015), which may be caused by a decrease in pollinator visits and an increase in seed predation (Franceschinelli et al, 2015). Fragmentation also resulted in reduced plant survival which could be attributed to higher desiccation and seedling predation (Alvarez-Aquino et al, 2004).…”
Section: Effects Of Habitat Degradation On Tmf Biodiversitymentioning
confidence: 99%